Superelastic Radiative Cooling Metafabric for Comfortable Epidermal Electrophysiological Monitoring - Dong, Jiancheng; Peng, Yidong; Zhang, Yiting; Chai, Yujia; Long, Jiayan; Zhang, Yuxi; Zhao, Yan; Huang, Yunpeng; Liu, Tianxi (Nano-Micro Letters, 2023)
Epidermal electronics with superb passive-cooling capabilities are of great value for both daytime outdoor dressing comfort and low-carbon economy. Herein, a multifunctional and skin-attachable electronic is rationally developed on a porous all-elastomer metafabric for efficient passive daytime radiative cooling (PDRC) and human electrophysiological monitoring. The cooling characteristics are realized through the homogeneous impregnation of polytetrafluoroethylene microparticles in the styrene–ethylene–butylene–styrene fibers, and the rational regulation of microporosity in SEBS/PTFE metafabrics, thus synergistically backscatter ultraviolet–visible–near-infrared light (maximum reflectance over 98.0%) to minimize heat absorption while efficiently emit human-body midinfrared radiation to the sky. As a result, the developed PDRC metafabric achieves approximately 17 °C cooling effects in an outdoor daytime environment and completely retains its passive cooling performance even under 50% stretching. Further, high-fidelity electrophysiological monitoring capability is also implemented in the breathable and skin-conformal metafabric through liquid metal printing, enabling the accurate acquisition of human electrocardiograph, surface electromyogram, and electroencephalograph signals for comfortable and lengthy health regulation. Hence, the fabricated superelastic PDRC metafabric opens a new avenue for the development of body-comfortable electronics and low-carbon wearing technologies. Highlights: 1 Efficient sunlight reflectivity and high mid-infrared radiation emissivity are simultaneously realized in a nonwoven metafabric via PTFE microparticle impregnation and thermal-fusion. 2 The metafabric achieves a maximum cooling effect of 17 °C and fully retains its passive cooling performance even under 50% stretching. 3 High-quality electrophysiological monitoring of ECG, sEMG and EEG is realized through compact and homogeneous encapsulation of liquid metal on the elastomeric fibers.